2016
DOI: 10.2174/1573406412666160506151032
|View full text |Cite
|
Sign up to set email alerts
|

cis-2-Alkenoic Acids as Promising Drugs for the Control of Biofilm Infections

Abstract: Microbes attached to surfaces and form biofilms where they are difficult to eradicate. Here they are embedded in a complex matrix of polymers and are much less sensitive against antibiotics or the immune system. This is a growing problem, especially for implants; hence, novel approaches are urgently needed to control biofilm infections. Many of these approaches interfere with the communication between the microbial cells required for biofilm formation and maintenance, a process known as quorum sensing. But mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Antibiofilm activities of fatty acids have only been reported for some cis-2-alkenoic acids with 10-14 carbon atoms [18] and some structural rules have been deduced. This has not yet been undertaken for C 18 -fatty acids; therefore, we tested several structurally related fatty acids for their ability to inhibit the biofilm formation of several bacterial pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…Antibiofilm activities of fatty acids have only been reported for some cis-2-alkenoic acids with 10-14 carbon atoms [18] and some structural rules have been deduced. This has not yet been undertaken for C 18 -fatty acids; therefore, we tested several structurally related fatty acids for their ability to inhibit the biofilm formation of several bacterial pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…However, using higher active chemical derivatives of ( 2 ) or ( 3 ) combined with an antibiotic could be a promising strategy to reduce specific staphylococci infections, since the bioactive compounds even in higher concentrations (1000 μg mL −1 ) did not display cytotoxicity against mammalian cells. Many studies demonstrated the efficacy of the use of quorum-quenching compounds together with antibiotics [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…aureus at concentrations of 64–16 μg mL −1 , with a MIC higher than 256 μg mL −1 , demonstrating the potential of this activity. Many molecular studies are necessary to discover the mechanisms of inhibition of biofilm formations, but if the cytochalasans are combined with antibiotics [47,48], this can be a promising strategy to treat staphylococcal infections.…”
Section: Discussionmentioning
confidence: 99%